Spectrum of Parotid Pathologies on Neck Ultrasound in A Tertiary Hospital of Western Nepal - Ghimire, Prasanna; Ghimire, Pragya Gautam; Poudel, Nabin; Bhandari, Shama; Singh, B. P. (Journal of Nepalgunj Medical College, 2018)
Objective: To investigate the spectrum of parotid pathologies on neck ultrasound and correlation with pathological findings. Materials and methods: A total of 41 patients with parotid swelling who had undergone neck ultrasound were included in this prospective study. Patients with history of previous neck ultrasound, recent surgery, bleeding diathesis or trauma, equivocal pathological findings were excluded from the study between June 2016 to May 2018. On-site fine needle aspiration cytology was performed by a pathologist who was blinded to the ultrasound findings. Results: Among the 41 patients, 41.5 % were males and58.5 % were females with age ranging from 1 to 76 years with a mean age of 37.31 years. Ultrasound was able to categorize lesions into benign and malignant with a sensitivity of 97.3 %, specificity of 50%. Pleomorphic adenoma was the most common pathology (46.3 %) followed by inflammatory conditions. Mucoepidermoid carcinoma was the most common malignant tumor constituting 7.3 % of the total cases. Conclusion: High resolution ultrasound can categorize parotid lesions with high degree of confidence in the hands of skilled radiologist. In equivocal cases, onsite fine needle aspiration by cytopathologist increases the diagnostic yield.